Legal protection to victims of transnational trafficking: the case of Ethiopia and Mozambique - Comoane, Paulo (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Mr Paulo Comoane, Faculty of Law, Universidade Eduardo Mondlane, Maputo, Moçambique.